2011
DOI: 10.1074/jbc.m111.219683
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Structural and Kinetic Rationale for Paralogous Copies of Phenylacetate-CoA Ligases from the Cystic Fibrosis Pathogen Burkholderia cenocepacia J2315

Abstract: The phenylacetic acid (PAA) degradation pathway is the sole aerobic route for phenylacetic acid metabolism in bacteria and facilitates degradation of environmental pollutants such as styrene and ethylbenzene. The PAA pathway also is implicated in promoting Burkholderia cenocepacia infections in cystic fibrosis patients. Intriguingly, the first enzyme in the PAA pathway is present in two copies (paaK1 and paaK2), yet each subsequent enzyme is present in only a single copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…The paa gene clusters that encode the enzymes responsible for PA catabolism are widely distributed in bacteria, and they are present in about 16% of completely sequenced bacterial genomes and in some archaea (Ferrández et al ., ; Olivera et al ., ; Mohamed et al ., ; Rost et al ., ; Alonso et al ., ; Bartolome‐Martín et al ., ; Kunishima et al ., ; Navarro‐Llorens et al ., 2005; 2008; Song et al ., ; Di Gennaro et al ., ; Hamlin et al ., ; Teufel et al ., ; Law and Boulanger, ; Patrauchan et al ., ; Sakamoto et al ., ). The paa pathway is controlled by a transcriptional repressor named PaaX or PaaR depending on the microorganism (Ferrández et al ., ; Olivera et al ., ; Navarro‐Llorens et al ., ; Hamlin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The paa gene clusters that encode the enzymes responsible for PA catabolism are widely distributed in bacteria, and they are present in about 16% of completely sequenced bacterial genomes and in some archaea (Ferrández et al ., ; Olivera et al ., ; Mohamed et al ., ; Rost et al ., ; Alonso et al ., ; Bartolome‐Martín et al ., ; Kunishima et al ., ; Navarro‐Llorens et al ., 2005; 2008; Song et al ., ; Di Gennaro et al ., ; Hamlin et al ., ; Teufel et al ., ; Law and Boulanger, ; Patrauchan et al ., ; Sakamoto et al ., ). The paa pathway is controlled by a transcriptional repressor named PaaX or PaaR depending on the microorganism (Ferrández et al ., ; Olivera et al ., ; Navarro‐Llorens et al ., ; Hamlin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…13,18,20,21 It has been hypothesized that in different CoA ligase enzymes, there is an equilibrium between conformations 1 and 2, and this equilibrium may be different for different CoA ligases during crystallization. 17 In the AuaEII crystal structure, the C-terminal domains of both monomers have elevated B-factors for the majority of residues except in the A10 core region, where Lys506 interacts with the anthraniloyl-AMP intermediate ( Figure S3).…”
mentioning
confidence: 99%
“…To date, many CoA ligase crystal structures have been solved that are bound with an acid substrate or aryl-adenylate intermediate, and these structures reveal residues that are important protein−substrate interactions. 13,17,18,21 An in depth comparison of the AuaEII crystal structure to the energy minimized AuaE homology model and six previously determined aryl:CoA ligase crystal structures reveal unprecedented insights into aryl substrate binding ( Figure 3; Table 1). The aryl-binding region of AuaEII consists of histidine (His324), isoleucine (Ile325), alanine (Ala293), and phenyalanine (Phe222).…”
mentioning
confidence: 99%
“…According to this finding, Law and Boulanger (2011) suggested that the more active, and substrate-versatile PaaK1 might be more beneficial during infection. However, our results show that PaaK1 (and possibly 3-OHPA as a PA degradation inducer) does not play a significant role in pathogenicity.…”
Section: Discussionmentioning
confidence: 94%
“…Given the evidence that 3-OHPA and 4-OHPA can be substrates of the PaaK enzymes (Law and Boulanger, 2011) we also considered that these compounds could be funneled exclusively through the PA catabolic pathway. B. cenocepacia K56-2 was grown in 3-OHPA or 4-OHPA as sole carbon sources and growth was recorded as final optical density.…”
Section: Resultsmentioning
confidence: 99%